Motives Affecting Fashion Consumers Behavior Toward Online Shopping During Covid-19 Pandemic - Genoveva, Genoveva; Dharmaatmaja, Hanif Rizky (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
COVID-19 has begun to penetrate Indonesia and has many impacts so that people can begin to adapt to this virus. People have experienced changes in their shopping behavior during this pandemic, especially in the fashion industry, many of them prefer to shop through online shops to avoid crowds and apply government regulations, with this policy requires adaptation. To sustain competitiveness, the fashion industry must understand customer behavior during this global crisis. This study aims to measure the influences between factors towards fashion consumption among the Z generation during the pandemic. Subjective norms and hedonic motivation were the independent variables in this research, perceived usefulness as a mediating variable, while the intention to purchase fashion online shopping during the pandemic was the dependent variable. This research was quantitative and surveys with 369 valid respondents. This study investigates how technology acceptance model (TAM) factors and social factors determine customer purchase intention. The research was conducted using questionnaires and analyzed using SEM, with SmartPLS Software. The finding suggests that perceived usefulness and subjective norms positively and significantly influenced intention to purchase fashion products online.